Thermodynamik Vorzeichen in der Literatur - Bredig, Georg
Chart of authors and their chosen variables used in thermodynamic calculations found in their respective publications. Authors listed are Rudolf Clausius (1822-1888), Josiah Willard Gibbs (1839-1903), Hermann von Helmholtz (1831-1894), James Clerk Maxwell (1831-1879), Jacobus Henricus van’t Hoff (1852-1911), Walther Nernst (1864-1941), Pierre Duhem (1861-1916), Max Planck (1858-1947), Georg Ferdinand Helm (1851-1923), Arthur von Oettingen (1836-1920), and Fritz Haber (1868-1934).
Keywords: Haber, Fritz, 1868-1934; Planck, Max, 1858-1947; Clausius, R. (Rudolf), 1822-1888; Gibbs, J. Willard (Josiah Willard), 1839-1903; Helmholtz, Hermann von, 1821-1894; Hoff, J. H. van 't (Jacobus Henricus), 1852-1911; Nernst, Walther, 1864-1941; Duhem, Pierre Maurice Marie, 1861-1916; Oettingen, Arthur Joachim von, 1836-1920; Bredig, Georg, 1868-1944; Chemists; Variables (Mathematics)